2019
DOI: 10.3390/cells8070667
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Allergen-Specific T Cell and IgE Reactivity to Different Preparations of Cow’s Milk-Containing Food Extracts

Abstract: Background: cow’s milk allergy (CM) is among the most common food allergies in young children and is often outgrown by adulthood. Prior to developing a tolerance to CM, a majority of CM-allergic children may tolerate extensively-heated CM. This study aims to characterize the IgE- and T cell-reactivity to unheated CM and the progressively more heated CM-containing foods. Methods: CM-containing food extracts from muffin, baked cheese, custard and raw, pasteurized CM commercial extract were tested for skin prick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Following CTV staining, cells were plated at 0.5 Â 10 6 cells per well in a final volume of 250 ml of media per well (corresponding to 2 Â 10 6 cells per milliliter final cell concentration) in a 96-, U-bottom well plate. We have previously shown that this cell concentration is suitable for in vitro expansion of Ag-specific T cells (26,27). Cells were stimulated with M. tuberculosisspecific MTB300 peptide pool (28) at 2 mg/ml (final concentration) or an equivalent DMSO concentration (0.3% final).…”
Section: Ex Vivo Nonnaive Cd4 T Cell Sortingmentioning
confidence: 99%
“…Following CTV staining, cells were plated at 0.5 Â 10 6 cells per well in a final volume of 250 ml of media per well (corresponding to 2 Â 10 6 cells per milliliter final cell concentration) in a 96-, U-bottom well plate. We have previously shown that this cell concentration is suitable for in vitro expansion of Ag-specific T cells (26,27). Cells were stimulated with M. tuberculosisspecific MTB300 peptide pool (28) at 2 mg/ml (final concentration) or an equivalent DMSO concentration (0.3% final).…”
Section: Ex Vivo Nonnaive Cd4 T Cell Sortingmentioning
confidence: 99%
“…The emulsifying properties of soy proteins stabilize the ingredients of meat stuffing into a homogeneous system. Soy proteins also improve the consistency and structure of finished products as a result of the formation of strong gels [1,4]. In addition, they reduce production costs while maintaining a high quality and increasing the efficiency of products, especially medium-ground and finely-ground sausages [5].…”
Section: Introductionmentioning
confidence: 99%